2020
DOI: 10.3324/haematol.2019.234542
|View full text |Cite
|
Sign up to set email alerts
|

Prospective isolation of radiation induced erythroid stress progenitors reveals unique transcriptomic and epigenetic signatures enabling increased erythroid output

Abstract: Massive expansion of erythroid progenitor cells is essential for surviving anemic stress. Research towards understanding this critical process, referred to as stress-erythropoiesis, has been hampered due to lack of specific marker-combinations enabling analysis of the distinct stress-progenitor cells capable of providing radioprotection and enhanced red blood cell production. Here we present a method for precise identification and in vivo validation of progenitor cells contributing to both steady-state and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 44 publications
0
14
1
Order By: Relevance
“…Steady-state erythropoiesis occurs at a constant rate in the BM, while anemia induces an extramedullary stress response in the spleen to rapidly produce large numbers of new erythrocytes [16,17]. The spleen weight of pRbdeficient mice was increased 2-fold compared with wild type ( Figure 1H,I).…”
Section: Erythroid-specific Deletion Of Prb Results In Mds-like Anemimentioning
confidence: 99%
“…Steady-state erythropoiesis occurs at a constant rate in the BM, while anemia induces an extramedullary stress response in the spleen to rapidly produce large numbers of new erythrocytes [16,17]. The spleen weight of pRbdeficient mice was increased 2-fold compared with wild type ( Figure 1H,I).…”
Section: Erythroid-specific Deletion Of Prb Results In Mds-like Anemimentioning
confidence: 99%
“…The findings by Singbrant et al 3 provide the field with an important tool to isolate stress-BFU-E in mice. This allows researchers to investigate stress erythropoiesis in a variety of mouse model systems that mimic disease con-ditions with acute anemia.…”
mentioning
confidence: 97%
“…Interestingly, the authors also found CD150 + CD9 + BFU-E progenitors in steady-state bone marrow but not the spleen, demonstrating that these markers are useful to identify BFU-E progenitors in both steady-state and stress conditions. Previous studies indicated that steady BFU-E migrate from the bone marrow to the spleen during stress erythropoiesis to become stress BFU-E, 12 while more recent findings suggest that endogenous splenic stress BFU-E during stress erythropoiesis are distinctive from steady BFU-E. 7 The CD150 + CD9 + BFU-E progenitors Singbrant et al 3 discovered in both steady state and stress conditions would be helpful to resolve this contradiction in future studies.…”
mentioning
confidence: 97%
See 2 more Smart Citations